Effect of high-intensity laser therapy on supraspinatus tendon elasticity in subacromial impingement syndrome: A double-blind randomized controlled study - Usgu, Serkan; Akbaş, Abuzer; Özdemir, Mustafa; Akbaş, Esin; Bulut, Hacı Taner; Usgu, Serkan (Springer Science and Business Media Deutschland GmbH)
This study primary aimed to evaluate the effect of high-intensity laser therapy (HILT) on the elasticity of the supraspinatus tendon in participants with subacromial impingement syndrome (SIS) and secondary aimed to evaluate the effect of HILT on pain and function. This randomized controlled double-blind study included 66 participants diagnosed with SIS and were randomly assigned into HILT group (HILT and physical therapy) and control group (sham HILT and physical therapy) and received 10 sessions (five days a week during two weeks). Supraspinatus tendon elasticity was measured by shear wave elastography (SWE). Pain and function were assessed by visual analog scale (VAS) and shoulder pain and disability index (SPADI), respectively. Measurements were made at baseline and after treatment. The minimal clinically important difference (MCID) was accepted as 1.37 for VAS and 13.2 for SPADI. There was no difference in SWE measurements before and after treatment in both groups (p > 0.05). VAS and SPADI showed clinically and statistically significant improvement in the HILT and control groups (p < 0.001). The r value for VAS and SPADI in the HILT group was calculated as 0.97; and 0.97 for VAS and 0.96 for SPADI in the control group. A statistically significant difference was found in VAS and SPADI in the HILT group compared to the control group (p = 0.010, p < 0.001, respectively). However, the differences were not clinically significant (mean differences 0.5 and 6.41, respectively). This study concluded that HILT applied together with physical therapy had no effect on tendon elasticity in the short term. Besides, HILT combined with physical therapy is statistically more effective in reducing pain and improving function than physical therapy alone.
Keywords: Elasticity imaging techniques; Laser therapy; Rotator cuff